Sulphur(lone pair)…π interactions with FAD in flavoenzymes - Silva, Rui F. N.; Sacco, Antonio Cesar S; Caracelli, Ignez; Zukerman-Schpector, Julio; Tiekink, Edward R. T. * (De Gruyter for Oldenbourgh Verlag, 2018)
The interactions of π-systems with lone-pairs of electrons are known and have been described in biological systems, involving lone-pairs derived from metals, metalloids, sulphur, oxygen and nitrogen. This study describes a bibliographic survey of the disulphide-bound sulphur(lonepair) interactions with -systems residing in the flavin adenine dinucleotide (FAD) cofactor oxidoreductase enzymes (flavoenzymes). Thus, of the 172 oxidoreductase enzymes evaluated for gamma-S(lone pair)…π(FAD) interactions, 96 proteins (56%) exhibited these interactions corresponding; 61% of 350 the constituent monomers featured at least one gamma-S(lone pair)…π(FAD) interaction. Two main points of association between the S(lone pair) and the isoalloxazine moiety of FAD were identified, namely at the centroid of the bond linking the uracil and pyrazine rings (60% ), and the centroid of the uracil ring (37%). Reflecting the nature of the secondary structure in three prominent classes of oxidoreductase enzymes: glutathione disulphide reductases (GR; 21 proteins), trypanothione disulphide reductases (TR, 14) and sulfhydryl oxidases (SOX, 22), the approach of the gamma-S(lone-pair) to the FAD residue was to the si-face of the isoalloxazine ring system, i.e. to the opposite side as the carbonyl residue, for all GR and TR examples, and to the re-face for all SOX examples. Finally, the attractive nature of the gamma-S(lone pair)…π(FAD) interactions was confirmed qualitatively by an examination of the non-covalent interaction plots.